2015
DOI: 10.1016/j.apjtm.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protective effect of cactus pear seed oil (Opuntia ficus-indica L. MILL.) against alloxan-induced diabetes in mice

Abstract: Based on theses results, CPSO can prevente alloxan-induced-diabetes by quenching free radicals produced by alloxan and inhibiting tissue injuries in pancreatic β-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 28 publications
3
27
1
1
Order By: Relevance
“…Among the action of the oil is the partial reduction of D‐glucose intestinal absorption. Successively, the same research group showed that the administration of the oil prevents alloxan‐induced diabetes by quenching the free radicals produced by alloxan and inhibiting tissue injuries in pancreatic β‐cells . These activities could be ascribed to the chemical composition of the oil, since it demonstrated that linoleic acid and oleic acid are the primary abundant compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Among the action of the oil is the partial reduction of D‐glucose intestinal absorption. Successively, the same research group showed that the administration of the oil prevents alloxan‐induced diabetes by quenching the free radicals produced by alloxan and inhibiting tissue injuries in pancreatic β‐cells . These activities could be ascribed to the chemical composition of the oil, since it demonstrated that linoleic acid and oleic acid are the primary abundant compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Opuntia spp. may exert an inhibitory effect on the oxidative environment generated by hyperglycemia, via their antioxidant components, and as suggested by a recent report by Berraaouan et al [93] who showed that cactus pear seed oil from O. ficus-indica L. Mill. prevents the development of alloxan-induced diabetes in mice by quenching the generation of ROS.…”
Section: Biological and Medical Properties Of Opuntia Spp In Chromentioning
confidence: 89%
“…prevent diabetes complications, and may even inhibit the disease's development . In mice, the OFI oil clearly shows protective effects against chemically induced (alloxan) diabetes mellitus . In detail, it acts by quenching free radicals produced by alloxan and inhibiting tissue injuries in pancreatic β‐cells.…”
Section: Uses and Benefitsmentioning
confidence: 99%